2009
DOI: 10.1186/1741-7015-7-68
|View full text |Cite
|
Sign up to set email alerts
|

STAT1-dependent expression of energy metabolic pathways links tumour growth and radioresistance to the Warburg effect

Abstract: BackgroundThe Signal Transducer and Activator of Transcription 1 (STAT1) has traditionally been regarded as a transmitter of interferon signaling and a pro-apoptotic tumour suppressor. Recent data have identified new functions of STAT1 associated with tumourigenesis and resistance to genotoxic stress, including ionizing radiation (IR) and chemotherapy. To investigate the mechanisms contributing to the tumourigenic functions of STAT1, we performed a combined transcriptomic-proteomic expressional analysis and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 32 publications
6
118
0
Order By: Relevance
“…Other studies have reported that the glycolytic pathway and the expression of glycolytic enzymes are associated with cancer radiosensitivity (26,27). We showed that ALDOA expression is positively correlated with the activity of glycolysis, with cell cycle progression and with ROS production.…”
Section: Discussionsupporting
confidence: 55%
“…Other studies have reported that the glycolytic pathway and the expression of glycolytic enzymes are associated with cancer radiosensitivity (26,27). We showed that ALDOA expression is positively correlated with the activity of glycolysis, with cell cycle progression and with ROS production.…”
Section: Discussionsupporting
confidence: 55%
“…Concurrently, overexpression of STAT1 led to the upregulation of IRDS genes (16). Stable knock-down of STAT1 led to the radiosensitization of SCC61 and nu61 tumors and downregulation of genes in the IRDS (16,17,20). Consistent with these results, suppression of STAT1 by fludarabine led to the radiosensitization of renal cell carcinoma cell lines (21).…”
Section: Clinical-translational Advancesmentioning
confidence: 76%
“…These changes were accompanied by alternative patterns of gene expression such as glycolysis/gluconeogenesis, the citric acid cycle, and oxidative phosphorylation. In particular, STAT1 expression had the most significant influence on the glycolysis/gluconeogenesis pathway, suggesting that STAT1-dependent expression of the energy metabolic pathway is associated with tumor growth and resistance to stress such as irradiation (22). We will therefore investigate metabolic pathways such as glycolysis/gluconeogeneis, the citric acid cycle, and oxidative phosphorylation in both Colon26L5-CUG2-shSTAT1 and Colon26L5-CUG2-shCon cells using microarrays in our next study.…”
Section: Discussionmentioning
confidence: 99%